Translation and Validation of the European Portuguese Version of the Quality of Life in Neurofibromatosis 1 Patients Scale (INF1-QoL) - Brito-Santana, Leonor (2024)
Introduction: The INF1-QoL questionnaire is an essential tool for assessing patients’ perceptions of their illness and its impact on their daily lives. This study aimed to obtain and validate the European Portuguese version of this questionnaire. Methods: The English version of INF1-QoL was translated using the “forward-backward” procedure. The questionnaire was administered to 78 adult patients with neurofibromatosis type 1. Results: The Portuguese-translated version of INF1-QoL showed good internal consistency (Cronbach’s alpha: 0.86); the mean total INF1-QoL score was 9.11 (SD 6.35), the median was 8.00, with a range of 0–31, and no significant correlations with age, gender or education were found. The mean total EuroQol score was 6.6 (SD: 1.55), the median was 6. Total INF1-QoL score correlated with total EuroQol score (r=0.839, p<0.001. The highest impact on QoL were moderate or severe problems with anxiety and depression (28%) and the negative effects of NF1 on role and outlook on life (49%). The mean clinical severity score was 2.96 (SD: 0.987) correlating with the total INF1-QoL score (r=0.279, p=0.019) and correlated with the total EuroQol score (r=0.251, p=0.036). The clinical severity was mild in 34 (49%), moderate in 22 (31%), and severe in 14 (20%) of individuals. Conclusion: Based on a detailed analysis of the results obtained, we found that the translated version of INF-QoL is a reliable and valid self-assessment screening tool for the Portuguese population with neurofibromatosis type 1.